Cyanidin-3-O-glucoside extracted from the Chinese bayberry (Myrica rubra Sieb. et Zucc.) alleviates antibiotic-associated diarrhea by regulating gut microbiota and down-regulating inflammatory factors in NF-κB pathway - Wang, Yanshuai; Chen, Jiebiao; Wang, Yue; Zheng, Fanghong; Qu, Meiyu; Huang, Ziwei; Yan, Jialang; Bao, Fangping; Li, Xian; Sun, Chongde; Zheng, Yixiong (Frontiers in Nutrition, 2022)
Chinese bayberry has been used to treat diarrhea in China for more than 2000 years, but the mechanism is not clear. Due to the extensive use of antibiotics, antibiotic-associated diarrhea (AAD) is becoming more and more common in clinic, but there is no effective drug for the treatment. The present study aimed to explore the therapeutic effect of Chinese bayberry on AAD for the first time, and explained the underlying mechanism from different aspects. The BALB/c mice model was established by intragastric administration of lincomycin (3 g/kg). Successfully modelled mice were treated with purified water, dried bayberry powder suspension (100 mg/kg), C3G suspension (40 mg/kg) and montmorillonite powder suspension (40 mg/kg) respectively. The changes of body weight, diarrhea index, diarrhea status score were recorded and calculated regularly. 16S rRNA gene sequencing, intestinal immunofluorescence and inflammatory factor detection were further performed. The treatment with dried bayberry powder suspension and C3G suspension could rapidly reduce the diarrhea score and diarrhea index, increase food intake and restore body weight gain. The gut microbiota richness and diversity were significantly increased after dried bayberry powder suspension and C3G suspension treatments, typically decreased bacterial genera Enterococcus and Clostridium senus stricto 1. In addition, intake of Chinese bayberry powder and C3G significantly decreased the level of p65 phosphorylation, and up-regulated the expression of intestinal tight junction protein claudin-1 and ZO-1. Chinese bayberry fruit had the effect of alleviating AAD, and C3G was supposed to play the predominant role. The mechanism was indicated to be related with restoring the homeostasis of gut microbiota, inhibiting the level of harmful bacteria and increasing the abundance of beneficial bacteria, down-regulating TNF-α, IL-6, and IL-12 factors to reduce inflammation, restoring intestinal tight junction proteins and reducing intestinal permeability.